Principal Leadership in Improving History Teacher Work Motivation at Senior High School of SMA Negeri 1 Banawa - Aksan; Charles Kapile; Mutawakkil; Lukman (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to analyze the principal's leadership in improving the work motivation of history teachers at SMA Negeri 1 Banawa and identify the inhibiting factors faced. This study used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the principal has made various efforts to improve the work motivation of history teachers through learning supervision, coaching, instilling discipline, providing role models, and verbal appreciation. In addition, the principal also strives to create a conducive work environment through good communication with teachers and education staff. However, the implementation of learning supervision has not been carried out consistently and has not been systematically documented, while the provision of awards to teachers is still limited and has not been done formally or continuously. This study also found several obstacles, including limited training and professional development, minimal award programs for outstanding teachers, and less than optimal innovation in history teacher learning. These conditions have an impact on teacher work motivation which is not optimal in the learning process. Nevertheless, the principal continues to strive to provide guidance and direction to improve the quality of learning and the quality of education at SMA Negeri 1 Banawa.